PERAN GURU PEMBIMBING EKSTRAKULIKULER DALAM MENINGKATKAN SIKAP KEPEMIMPINAN SANTRI PONDOK PESANTREN DARUNNA’IM YAPIA BOGOR - Muhammad Zul Fikri; Oking Setia Priyatna; Ahmad Mulyadi Kosim (KOLONI, 2022)
This study aims to determine the role of extracurricular supervising teachers in improving the leadership attitudes of the Darunna'im Yapia Islamic Boarding School students. The research method used is a qualitative research method. Qualitative research is a descriptive research and the results use conclusions based on a situation. The results showed that extracurricular supervising teachers played a role in improving the leadership attitude of the Darunna'im Yapia Islamic Boarding School students. In addition to playing a role in cultivating the interests and talents of students, extracurricular supervising teachers also play a role in improving the leadership attitudes contained in students which have previously been grown through academic activities carried out by students in their daily lives at the boarding school. Extracurricular activities themselves can also make students more enthusiastic with more motivation and experience in the organization. Therefore, extracurricular supervising teachers play a role in improving leadership attitudes in the students of Darunna'im Yapia Islamic Boarding School. Keywords: teacher's role, leadership attitude, organization